Country Partnership Framework for Islamic Republic of Afghanistan for the Period FY17 to FY20 - World Bank (World Bank, Washington, DC, 2016)
This Country Partnership Framework (CPF) covers the four-year period, from FY2017 through FY2020. The World Bank Group (WBG) has relied up to now on a series of short two-year Interim Strategy Notes (ISNs) to capture its strategic engagement. The CPF sets out a medium-term strategic framework that is intended to be flexible and responsive to the rapidly evolving situation in Afghanistan. It is aligned with country priorities as outlined in the government’s “Realizing Self-Reliance: Commitments to Reforms and Renewed Partnership” paper presented to the London Afghanistan Conference in December 2014 and draft National Peace and Development Framework (ANPDF). It is based on the findings and recommendations of the Systematic Country Diagnostic (SCD), which was completed in February 2016.